Electrochemical Nitric Oxide Reduction on Metal Surfaces. Issue 40 (31st August 2021) - Wan, Hao; Bagger, Alexander; Rossmeisl, Jan
Abstract: Electrocatalytic denitrification is a promising technology for removing NO x species (NO3 −, NO2 − and NO). For NO x electroreduction (NO x RR), there is a desire for understanding the catalytic parameters that control the product distribution. Here, we elucidate selectivity and activity of catalyst for NO x RR. At low potential we classify metals by the binding of *NO versus *H. Analogous to classifying CO2 reduction by *CO vs. *H, Cu is able to bind *NO while not binding *H giving rise to a selective NH3 formation. Besides being selective, Cu is active for the reaction found by an activity‐volcano. For metals that does not bind NO the reaction stops at NO, similar to CO2 ‐to‐CO. At potential above 0.3 V vs. RHE, we speculate a low barrier for N coupling with NO causing N2 O formation. The work provides a clear strategy for selectivity and aims to inspire future research on NO x RR. Abstract : An illustration of selectivity and activity on metals for nitric oxide reduction reaction is presented. Both selectivity and activity of NO reduction has been indicated by *N adsorption energy. There is a very little window to find both selective and active catalyst for the NO reduction in the volcano.